Effect of milk on team sport performance after exercise-induced muscle damage - Cockburn, E.; Bell, P. G.; Stevenson, E. (Medicine & Science in Sports & Exercise, 2013)
Introduction: Exercise-induced muscle damage (EIMD) leads to increases in intramuscular proteins observed in the blood stream and delayed onset of muscle soreness, but crucial for athletes are the decrements in muscle performance observed. Previous research has demonstrated that carbohydrate-protein supplements limit these decrements; however, they have primarily used isokinetic dynamometry, which has limited applicability to dynamic sport settings. Therefore, the aim of this study was to investigate the effects of a carbohydrate-protein milk supplement consumed after muscle-damaging exercise on performance tests specific to field-based team sports.